2015
DOI: 10.1128/jcm.02827-14
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella, a Common Cause of Endocarditis: a Report on 106 Cases and Review

Abstract: Bartonella spp. are fastidious bacteria that cause blood culture-negative endocarditis and have been increasingly reported. In this study, we included all patients retrospectively and prospectively diagnosed with Bartonella endocarditis in our French reference center between 2005 and 2013. Our diagnosis was based on the modified Duke criteria and microbiological findings, including serological and PCR results. To review the published literature, we searched all human Bartonella endocarditis cases published in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
185
5
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(217 citation statements)
references
References 35 publications
6
185
5
9
Order By: Relevance
“…Due to the relative abundance of bacterial DNA in valve tissue versus blood, testing of cardiac valve tissue with organism-specific PCR assays is more sensitive than testing blood or serum. For example, in one study, sensitivity of a Bartonella PCR assay on valve tissue was 92% (48/52) compared to 33% (20/60) and 36% (25/70) sensitivity in blood and serum, respectively (26). Nevertheless, a PCR result on blood may be helpful when positive.…”
Section: Evaluation Of Excised Cardiac Valvular Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the relative abundance of bacterial DNA in valve tissue versus blood, testing of cardiac valve tissue with organism-specific PCR assays is more sensitive than testing blood or serum. For example, in one study, sensitivity of a Bartonella PCR assay on valve tissue was 92% (48/52) compared to 33% (20/60) and 36% (25/70) sensitivity in blood and serum, respectively (26). Nevertheless, a PCR result on blood may be helpful when positive.…”
Section: Evaluation Of Excised Cardiac Valvular Tissuementioning
confidence: 99%
“…In cases where both broad-range bacterial PCR and organism-specific PCR were performed for the diagnosis of endocarditis, 62% (76/123) of specimens were positive by targeted PCR only, while only 2 specimens were positive by broad-range PCR only (34). For the diagnosis of Bartonella endocarditis, Bartonella-specific PCR applied to cardiac valve tissue was positive in 92% (48/52) of cases while broad-range PCR of valve tissue identified Bartonella in only 60% (21/35) of cases (26). Therefore, for diagnosis of culture-negative endocarditis, broad-range bacterial PCR should not be performed in lieu of organism-specific PCR.…”
Section: Evaluation Of Excised Cardiac Valvular Tissuementioning
confidence: 99%
“…1,2,5 Congenital heart disease and prosthetic valve repair have been identified as risk factors for the development of B. henselae endocarditis, particularly in the pediatric population. 4,7 Serology, polymerase chain reaction, or histology is needed to identify Bartonella spp., when suspected. 2 IE may present with renal comorbidities such as perinephric abscesses, infarction from emboli, or glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Bartonella henselae usually affects patients with previous valvular disease, prosthetic or bioprosthetic valves, or congenital heart defects. 3,4 In rare instances, patients with Bartonella endocarditis may develop glomerulonephritis. 5,6 …”
mentioning
confidence: 99%
“…or Coxiella burnetii. However, Edouard et al showed that an IgG titer greater than 1:800 (in an immunofluorescence antibody assay) or a positive western blot can be considered as major Duke criteria indicating Bartonella endocarditis [14].…”
Section: Discussionmentioning
confidence: 99%